2020
DOI: 10.1021/acscatal.0c02455
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Computational Studies of the Mechanism of Dehydrogenative Borylation of Terminal Alkynes Catalyzed by PNP Complexes of Iridium

Abstract: Iridium complexes supported by four different diarylamido/bis(phosphine) PNP ligands have been studied as catalysts for the dehydrogenative borylation of terminal alkynes (DHBTA). Experimental mechanistic investigations on a representative ligand system established that the reaction rate is zeroth order in the concentration of the borylating agent HBpin, first order in [alkyne] and in [Ir], and inverse first order in [H 2 ]. These findings are understood as arising from the formation of the saturated, 18-elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…In the 31 P{ 1 H} NMR spectrum in C 6 D 6 at room temperature, four 31 P NMR resonances were observed. 31 P NMR resonances at δ 148.7 and 147.9 were assigned to P−O of two isomers, respectively, and 31 P NMR resonances at δ 61.2 and 60.6 were assigned to P−N of two isomers, respectively. The 1 H NMR spectrum also showed two sets of resonances that correspond to two isomers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the 31 P{ 1 H} NMR spectrum in C 6 D 6 at room temperature, four 31 P NMR resonances were observed. 31 P NMR resonances at δ 148.7 and 147.9 were assigned to P−O of two isomers, respectively, and 31 P NMR resonances at δ 61.2 and 60.6 were assigned to P−N of two isomers, respectively. The 1 H NMR spectrum also showed two sets of resonances that correspond to two isomers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It should also be noted that the SiNN-and PNP-supported Ir pincer catalysts for DHBTA do not catalyze aromatic C−H borylation and furthermore operate by different mechanisms in DHBTA. 27,31 On the whole, there exists a remarkable mechanistic diversity of possible C−H borylation pathways with Ir, depending on the supporting ligands and the substrate.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of DHBTA catalysis by the SiNN-and PNPsupported Ir complexes has been thoroughly investigated computationally and experimentally. 12,13 Other groups reported DHBTA catalysts based on Zn, 14,15 Cu, 16 and Fe, 17 and we reported a Pd-based DHBTA catalyst (Scheme 1). 18 Chirik et al also reported a Co catalyst that produces alkynylboronates from terminal alkynes en route to 1,1-diborated alkene products.…”
mentioning
confidence: 72%